2004
DOI: 10.1023/b:bigi.0000026631.46010.ca
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Allozyme Markers for Appalachian Wood-Feeding Cockroaches (Dictyoptera: Cryptocercidae)

Abstract: Members of the genus Cryptocercus are wood-feeding cockroaches that live in the temperate forests. Nine species are recognized in the genus worldwide: two in eastern Eurasia, two in China, and five in the United States. Within the United States, one species occurs in the Pacific Northwest and four occur in the Appalachian Mountains. Previous studies have revealed the presence of potential zones of overlap in distribution among the Appalachian species, raising the possibility of hybridization among them. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…For example, the species descriptions of Burnside et al (2000) characterized C. wrighti as having a male diploid chromosome number of 2n=45; individuals with a chromosome number of 2n=43 were considered C. punctulatus (see Table 4 of Burnside et al, 2000). Recently, however, Aldrich et al (2004a) indicated that a substantial population of cockroaches with the allozyme and molecular characteristics of C. wrighti have the same chromosome number as C. punctulatus ; they nonetheless considered this population C. wrighti . A recently published paper purporting to support the species definitions of Burnside et al (2000) with morphological data (Aldrich et al , 2004b) did not address this discrepancy, nor did it reconcile discordance with morphological data already in the literature ( e.g ., Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the species descriptions of Burnside et al (2000) characterized C. wrighti as having a male diploid chromosome number of 2n=45; individuals with a chromosome number of 2n=43 were considered C. punctulatus (see Table 4 of Burnside et al, 2000). Recently, however, Aldrich et al (2004a) indicated that a substantial population of cockroaches with the allozyme and molecular characteristics of C. wrighti have the same chromosome number as C. punctulatus ; they nonetheless considered this population C. wrighti . A recently published paper purporting to support the species definitions of Burnside et al (2000) with morphological data (Aldrich et al , 2004b) did not address this discrepancy, nor did it reconcile discordance with morphological data already in the literature ( e.g ., Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetically assigned chromosomal races have been used to identify other locations where two races might co-occur. For instance, Aldrich et al (2004) identified three potential locations of co-occurrence, one of which was within *30 km of the focal rotting log identified in the present study. However, despite extensive sampling and numerous molecular studies spanning the past 20 years, the present study is the first to detect true syntopy in the C. punctulatus species complex.…”
Section: Resultsmentioning
confidence: 64%
“…There are also conflicting reports on the spatial distributions of the four races, which have been described as either strictly allopatric (Burnside et al 1999), parapatric (Nalepa et al 2002;Everaerts et al 2008), or sympatric (Steinmiller et al 2001). One likely reason for this uncertainty is because the majority of previous studies with dense (i.e., population-level) sampling have based race assignment on just one individual per site (e.g., Steinmiller et al 2001;Aldrich et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, since no reliable morphological differences were apparent, the only diagnostic characters presented by the authors were mtDNA nucleotides (originally seven species-specific mutations, but subsequently reduced to four by Steinmiller, Kambhampati & Brock, 2001), and the descriptions were based on few reliably classified individuals (i.e., those for which both karyotype and mtDNA sequence were determined). Furthermore, species diagnosis on the basis of mtDNA has been applied inconsistently (e.g., Aldrich, Krafsur & Kambhampati, 2004), and the geographic origin of some type material is unclear (Nalepa et al, 2002). Since these issues remain unresolved, the original taxon name, C. punctulatus , is used here.…”
Section: Methodsmentioning
confidence: 99%
“…Given that copulation between adults likely takes place within the same gallery of the rotting log in which the pair later raise their family, mate pairs have been considered monogamous since opportunities for extra-pair copulation are few (but see Nalepa & Grayson, 2011). Although the spatial demarcation of family groups is difficult, sampling strategies employed in several molecular studies of C. punctulatus have used a single random sample (e.g., Steinmiller, Kambhampati & Brock, 2001; Aldrich, Krafsur & Kambhampati, 2004; Aldrich, Zolnerowich & Kambhampati, 2004). Depending on the question at hand, this may be adequate.…”
Section: Introductionmentioning
confidence: 99%